PWE-341 The potential role of fibroblast growth factor 7 (fgf-7) in field cancerisation of colon cancer. (22nd June 2015) - Patel, A; Williams, N; Azharian, S; Murphy, A; McTernan, P; Tripathi, G; Arasaradnam, R
Abstract : Introduction: Recent analyses have revealed that mutations found in colorectal cancer (CRC) occur long before the onset of a clinically visible lesion, 1 suggesting, that the macroscopically normal mucosa (MNM) around a neoplastic lesion is biologically altered. Our previous findings indicated that FGF7 is upregulated in the adjacent MNM in patients whose tumours also show increased FGF7 expression supporting the concept of field cancerisation. 2 The study aims to determine if the changes seen in gene expression translate to activation of the FGF7 signalling pathway in MNM of cancer patients. The first downstream target of FGF7 is FRS2 which is phosphorylated upon binding of FGF7 to its receptor, FGFR2. Method: Mucosal pinch biopsies were taken from the rectum and caecum at time of colonoscopy for healthy controls. For CRC patients, tissue samples were taken from the tumour, adjacent to the tumour and at the resection margin of the specimen. Healthy controls were age and sex matched to CRC patients. Western blot analysis was used to assess protein expression of FRS2 and phospho FRS2. The Mann-Whitney U test was used to assess statistical significance with p value <0.05 considered significant. Results: 48 patients were recruited (27 M: 21 F, median age 71 years (range 48–86 years)); 16 patients with CRC and 32 healthy controls. Gene expression analysis had shown that FGF7 is upregulated in 6/19 cancers; this was associated with a significant upregulation of FGF7 in adjacent mucosa compared with cancers where FGF7 was downregulated (mean fold change 3.62 vs. 0.95, p = 0.018). 4/6 tumours where FGF7 was upregulated showed increased expression ratio of FRS2:pFRS2 and all 8 tumours where it was downregulated had a lower ratio of protein expression. There was significant upregulation of FRS2:pFRS2 in the adjacent mucosa of tumours with upregulation of FGF7 compared with those where it was downregulated (mean fold change 1.31 vs. 0.79, p = 0.014). Conclusion: The changes seen in gene and protein expression suggest that the FGF7 signalling cascade is dysregulated in tumour tissue and the adjacent MNM. FGF7 may contribute to preconditioning of colonic mucosa for further malignant change. Disclosure of interest: None Declared. References: Tsao JL, Yatabe Y, Salovaara R, Järvinen HJ, Mecklin JP, Aaltonen LA, Tavaré S, Shibata D. Genetic reconstruction of individual colorectal tumour histories. Proc Natl Acad Sci USA 2000;97(3):1236–1241 Patel A, Williams N, Nwokolo C, Tripathi G, Arasaradnam R. PWE-001 Field Cancerisation Theory in Colorectal Cancer (CRC): What role do fibroblast growth factors have?. Gut 2014;63(Suppl 1):A121